Elevated Level of CD4+ T Cell Immune Activation in Acutely HIV-1-Infected Stage Associates With Increased IL-2 Production and Cycling Expression, and Subsequent CD4+ T Cell Preservation - Xia, Huan; Jiang, Wei; Zhang, Xin; Qin, Ling; Su, Bin; Li, Zhen; Sun, Jianping; Zhang, Yonghong; Zhang, Tong; Lu, Xiaofan; Wu, Hao (Frontiers in Immunology, 2018)
Persistent immune activation is a striking consequence of HIV-1 infection, and a driving force of CD4+ T cell depletion and AIDS events during chronic infection. High level of T cell immune activation associates with antiretroviral therapy (ART)-treated clinical outcomes in chronically HIV-1-infected patients. However, the role of T cell activation during acute infection stage in subsequent CD4+ T cell decline in the absence of ART treatment is unknown. In this study, we enrolled 26 acutely HIV-1-infected patients in the absence of ART treatment from a prospective acute HIV-1 infection cohort in Beijing (PRIMO). A comprehensive analysis of CD4+ and CD8+ T cell immune activation during acute infection stage and the clinical outcomes was studied. We found that patients with higher level of CD4+ T cell activation (%CD38+HLA-DR+CD4+ T cells) exhibited more effective function (%IL-2 production and %ki67 expression) in CD4+ T cells compared to those from patients without increased T cell activation at the acute phase. Direct correlations were observed between CD4+ T cell activation and the percentages of IL-2-producing or ki67-expressing CD4+ T cells in patients at the acute phase of infection. Importantly, the increased levels of CD4+ T cell immune activation, IL-2 production, and cycling expression during acute infection were associated with less decline of CD4+ T cell after 2 years of infection. However, immune exhaustion molecules in acute infection including CD160, TIGIT, PD-1, and TIM-3 were not associated with the CD4+ T cell depletion. These significant associations of CD4+ T cell activation were not demonstrable for CD8+ T cell activation at the acute phase. Taken together, our observations provide new insight into the possible role of T cell activation in preventing CD4+ T cell depletion during acute HIV-1 infection.